2012
DOI: 10.5194/acp-12-9441-2012
|View full text |Cite
|
Sign up to set email alerts
|

The impact of differences in large-scale circulation output from climate models on the regional modeling of ozone and PM

Abstract: Climate change may have an impact on air quality (ozone, particulate matter) due to the strong dependency of air quality on meteorology. The effect is often studied using a global climate model (GCM) to produce meteorological fields that are subsequently used by chemical transport models. However, climate models themselves are subject to large uncertainties and fail to reproduce the present-day climate adequately. The present study illustrates the impact of these uncertainties on air quality. To this end, outp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
54
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 39 publications
12
54
0
Order By: Relevance
“…Several other studies have focused only on the regional impact of climate change (Langner et al, 2012a, b;Andersson and Engardt, 2010;Manders et al, 2012;Hedegaard et al, 2008Hedegaard et al, , 2013Katragkou et al, 2011). They found a general increase in ozone concentrations owing to increasing biogenic emissions and favourable conditions for the build-up of ozone pollution as a result of increased temperature, more frequent summer blocking and heat waves and increased short-wave radiation.…”
Section: Role Of Biogenics In the Formation Of Ozonementioning
confidence: 99%
See 1 more Smart Citation
“…Several other studies have focused only on the regional impact of climate change (Langner et al, 2012a, b;Andersson and Engardt, 2010;Manders et al, 2012;Hedegaard et al, 2008Hedegaard et al, , 2013Katragkou et al, 2011). They found a general increase in ozone concentrations owing to increasing biogenic emissions and favourable conditions for the build-up of ozone pollution as a result of increased temperature, more frequent summer blocking and heat waves and increased short-wave radiation.…”
Section: Role Of Biogenics In the Formation Of Ozonementioning
confidence: 99%
“…Bloomer et al (2009) estimated the magnitude of these effects from surface ozone observations over the US at about 2.2 ppb per degree Celcius and Pfister et al (2014) showed increasing summertime ozone levels under various climate scenarios. These effects have been quantified over Europe in several model studies Meleux et al, 2007;Langner et al, 2012a, b;Andersson and Engardt, 2010;Manders et al, 2012;Hedegaard et al, 2008Hedegaard et al, , 2013bKatragkou et al, 2011). The general order of magnitude of the climate penalty over Europe is a few ppb by the middle of the century.…”
Section: Hemispheric Transport Of Ozone and It Precursors In The Polimentioning
confidence: 99%
“…Precipitation is highly variable in time and space, and fields computed by climate models often do not capture the frequency and/or intensity distribution of events correctly (Piani et al, 2009;Manders et al, 2012;Dai, 2006). Additionally, sub-grid topographic features may place large controls on the distribution of precipitation events (Leung and Ghan, 1998).…”
Section: Snow Correction Methodsmentioning
confidence: 99%
“…A more elaborate description can be found in the model documentation (Manders-Groot et al, 2016a) 4.1 Domain, grid LOTOS-EUROS is a regional model on a regular longitudelatitude grid. It is typically used with a resolution of 0.5 • × 0.25 • on a domain covering most of Europe and the Mediterranean Sea, but can be applied anywhere and with arbitrary grid resolution, provided that the horizontal resolution is not smaller than about 3 km.…”
Section: Model Descriptionmentioning
confidence: 99%
“…The gas-phase chemistry is a condensed version of CBM-IV (Gery et al, 1989), with some modifications in reaction rates, 4152 A. M. M. Manders et al: Curriculum vitae of the LOTOS-EUROS (v2.0) chemistry transport model and can be found in Manders-Groot et al (2016a). A kinetic pre-processor is used which makes it relatively straightforward to add or modify chemical reactions.…”
Section: Chemistrymentioning
confidence: 99%